Psychology - Carlson, Neil R., 1942-; Martin, G. Neil.; Buskist, William (Harlow, England : Pearson, 2004)
Covering the aspects of 1st year undergraduate psychology courses, this book emphasises how the various sub-disciplines in psychology are interrelated. It covers research and the application of that research to real-life problems and situations. It includes a companion web Site and lecture resources. It engages, informs, and facilitates debate.
The authors Acknowledgements -- THE SCIENCE OF PSYCHOLOGY -- RESEARCH METHODS IN PSYCHOLOGY -- EVOLUTION, GENETICS, AND BEHAVIOUR -- PSYCHOBIOLOGY AND NEUROSCIENCE -- SENSATION -- PERCEPTION -- LEARNING AND BEHAVIOUR -- MEMORY. 9. CONSCIOUSNESS -- LANGUAGE -- INTELLIGENCE AND THINKING -- DEVELOPMENTAL PSYCHOLOGY -- MOTIVATION AND EMOTION -- PERSONALITY -- SOCIAL COGNITIONS AND ATTITUDES -- INTERPERSONAL AND GROUP PROCESSES -- HEALTH PSYCHOLOGY -- ABNORMAL PSYCHOLOGY
Includes bibliographical references (p. [822]-895) and index.
1
Keywords: Psychology